Dialog Gereja-Gereja dalam Merawat Alam Tanah Batak untuk Membangun Kesadaran Lingkungan dan Kolaborasi Antar Umat - Ben Sitompul; Bona Ventro Simatupang; Eryn Napitupulu; Niar Sagala; Syerafin Silaban; Riris Johanna Siagian (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2025)
The worsening ecological crisis, such as the floods that hit Parapat, demands a serious response from various elements of society, including religious institutions. This article highlights the role of the Church, particularly Huria Kristen Batak Protestan (HKBP), in caring for nature in Tanah Batak as a form of faith and social responsibility. Using theological and socio-cultural approaches, this study analyzes the contribution of HKBP teachings and Pope Francis' call in the encyclical Laudato Si' to the ecological awareness of the people. It emphasizes that the HKBP doctrine of the wholeness of creation and community-based ecological movements can be transformative solutions to environmental degradation. Through a case study of flooding in Parapat, this article demonstrates the urgency of church involvement in ecological advocacy and environmental education, and the importance of synergy between faith, Batak culture, and concrete action for the sustainability of God's creation. The HKBP's teachings on the wholeness of creation align closely with Pope Francis’ encyclical Laudato Si’, which calls for a radical shift in how humanity perceives and interacts with nature. By emphasizing the interconnectedness of all life, the HKBP doctrine encourages its followers to view environmental stewardship not only as a moral obligation but as an essential expression of faith. This view aligns with Pope Francis' call for an "ecological conversion," urging individuals and communities to recognize their role in caring for God's creation. Through the case study of flooding in Parapat, this article illustrates the real-world implications of ecological negligence and the importance of church involvement in ecological advocacy. The HKBP, along with other religious and community-based movements, can spearhead efforts to integrate environmental education into their teachings and local initiatives.